A MIXED INTEGER-PROGRAMMING MODEL FOR PERIODIC ROUTING OF SPECIAL VESSELS IN OFFSHORE OIL INDUSTRY - Eshraghniaye Jahromi, Abdolhamid; Ighani Yazdeli, Roohollah (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--> <span style="font-size: 10.0pt; mso-ascii-font-family: "Times New Roman"; mso-ascii-theme-font: major-bidi; mso-hansi-font-family: "Times New Roman"; mso-hansi-theme-font: major-bidi; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: major-bidi;">In order to maintain the production of offshore oil wells, National Iranian Oil Company periodically services facilities and equipment located in oil wellheads with mobile wellhead servants. It also gives technical supports to oil wellheads and mobile wellhead servants with supporter vessels. Due to supply limitations, there are fewer special vessels (namely supporter vessels and mobile wellhead servants) compared to the number of oil wellheads. Failure to service oil wellheads by special vessels and also failure to technically support mobile wellhead servants by supporter vessels based on a predetermined plan, will lead to considerable loss in production performance of oil wells and hence higher costs. Finding best plan to service oil wellheads considering traveling and shortage costs, we propose a mixed integer programming model and a heuristic algorithm for the problem. Computational results on both simulated and real life instances are reported and performance of the proposed algorithm is evaluated. <span style="mso-ascii-font-family: "Times New Roman"; mso-ascii-theme-font: major-bidi; mso-hansi-font-family: "Times New Roman"; mso-hansi-theme-font: major-bidi; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US;"> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->